2021
DOI: 10.1155/2021/8889195
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‐128 Ameliorates Ang II‐Induced Cardiac Remodeling via SIRT1/PIK3R1 Multiple Targets

Abstract: Recent studies reported that miR-128 was differentially expressed in cardiomyocytes in response to pathologic stress. However, its function and mechanism remain to be fully elucidated. The aim of the present study was to investigate the role of miR-128 in chronic angiotensin II (Ang II) infusion-induced cardiac remodeling and its underlying mechanism. The cardiac remodeling and heart failure in vivo were established in C57BL/6 mice by chronic subcutaneous Ang II delivery. Knocking down miR-128 was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…As a result, these enzymes might also prove valuable as therapeutic targets [ 46 ]. The role of miRNA in the regulation of PI3KR1 was also described in the study by Zhan H. et al [ 47 ], which showed that the downregulation of miR-128 restored PIK3R1 mRNA and the protein levels induced by angiotensin II, being accompanied by upregulation of the levels of phospho-Akt and -mTORC1 in vivo and in vitro. Moreover, alteration of the PIK3R1/Akt/mTORC1 pathway was negatively correlated with autophagy, while mTORC1 blocker rapamycin abolished miR-128 antagomir’s inhibition of angiotensin II-induced apoptosis and ROS production.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…As a result, these enzymes might also prove valuable as therapeutic targets [ 46 ]. The role of miRNA in the regulation of PI3KR1 was also described in the study by Zhan H. et al [ 47 ], which showed that the downregulation of miR-128 restored PIK3R1 mRNA and the protein levels induced by angiotensin II, being accompanied by upregulation of the levels of phospho-Akt and -mTORC1 in vivo and in vitro. Moreover, alteration of the PIK3R1/Akt/mTORC1 pathway was negatively correlated with autophagy, while mTORC1 blocker rapamycin abolished miR-128 antagomir’s inhibition of angiotensin II-induced apoptosis and ROS production.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, alteration of the PIK3R1/Akt/mTORC1 pathway was negatively correlated with autophagy, while mTORC1 blocker rapamycin abolished miR-128 antagomir’s inhibition of angiotensin II-induced apoptosis and ROS production. Therefore, miR-128 downregulation alleviated the angiotensin-II-induced elevation of autophagy, likely via the PIK3R1/Akt/mTORC1 pathway in cardiomyocytes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these selected miRNAs, miR-128-3p has been reported to be involved in the regulation of various heart diseases. The expression of miR-128-3p in the myocardium was found to be increased during cardiac hypertrophy and heart failure [ 42 , 43 ], while decreased during ischemia–reperfusion cardiac injury [ 44 ]. In the present study, the decreased miR-128-3p level was also detected in the heart tissues of T2DM rats, but its role in DCM has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, treatment with EX527 abolished the beneficial effect of miR-128 downregulation (Zhan et al, 2021). Taurine, a free intracellular β-amino acid, has cardioprotective effects.…”
Section: Regulation Of the Tumor Suppressor Gene P53mentioning
confidence: 95%